The Effect of Village Regeneration on Settlement and Residential Satisfaction: Change to Tourist Attraction from Residential Area. Issue 3 (1st September 2016) - Kim, Minkyun; Park, Jina
Abstract : The aim of this study is to find out how village regeneration of Ewha Village, a place that has become a tourism attraction, affected its residential satisfaction and settlement. Thus, through surveys conducted on residents of Ehwa Village, effects of village regeneration on settlement and on residential satisfaction were analyzed. Results of the survey showed that while the residents are satisfied with installation and maintenance of infrastructure, betterment in castle maintenance, and residential activity, they were unsatisfied with tourism vitalization, increased value of property, overall residential satisfaction, and also with settlement. The results imply that the residents are satisfied with physical maintenance of the residential environment but not with various problems caused by tourists. Path analysis results suggest that residential satisfaction is directly affected by infrastructure maintenance, improvement in castle maintenance, tour vitalization, and public management. Furthermore, while factors of village regeneration did not have any direct effect on settlement, installation and maintenance of infrastructure, tourism vitalization, and public management did indirectly affect settlement through residential satisfaction.